Determination of Financial Factors on Firm Value - Kurniawan, Yogi Ade Tia; Hartono, Ulil; Haryono, Nadia Asandimitra (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2025)
This study aims to analyze the impact of Liquidity, Solvency, Profitability, and Activity on Company Value in food and beverage manufacturing companies listed on the IDX for the 2019–2022 period. The research employs a quantitative, causal associative approach using secondary data from company financial statements. A purposive sampling method was used, resulting in a sample of 24 companies, and the data were analyzed using multiple linear regression. The results show that simultaneously, the independent variables influence Company Value. Partially, the Liquidity variable (proxies: current ratio, quick ratio, and cash ratio) significantly affects Company Value (PBV). For Solvency, the debt-equity ratio (DER) and long-term debt-equity ratio (LTDtER) significantly affect Company Value, while the debt-asset ratio (DAR) does not. In terms of Profitability, return on equity (ROE) and return on assets (ROA) have significant effects, but net profit margin (NPM) does not. Lastly, under the Activity variable, inventory turnover (PPe) significantly affects Company Value, while accounts receivable turnover (PPi) does not. These findings underscore the importance of financial performance metrics in describing a company’s ability to meet obligations, achieve profitability, and manage asset turnover. Such insights are valuable for companies in understanding how their financial performance impacts Company Value.